Cell cycle–related metabolism and mitochondrial dynamics in a replication-competent pancreatic beta-cell line. Issue 21 (2nd November 2017) - Montemurro, Chiara; Vadrevu, Suryakiran; Gurlo, Tatyana; Butler, Alexandra E; Vongbunyong, Kenny E; Petcherski, Anton; Shirihai, Orian S; Satin, Leslie S; Braas, Daniel; Butler, Peter C; Tudzarova, Slavica
ABSTRACT: Cell replication is a fundamental attribute of growth and repair in multicellular organisms. Pancreatic beta-cells in adults rarely enter cell cycle, hindering the capacity for regeneration in diabetes. Efforts to drive beta-cells into cell cycle have so far largely focused on regulatory molecules such as cyclins and cyclin-dependent kinases (CDKs). Investigations in cancer biology have uncovered that adaptive changes in metabolism, the mitochondrial network, and cellular Ca 2+ are critical for permitting cells to progress through the cell cycle. Here, we investigated these parameters in the replication-competent beta-cell line INS 832/13. Cell cycle synchronization of this line permitted evaluation of cell metabolism, mitochondrial network, and cellular Ca 2+ compartmentalization at key cell cycle stages. The mitochondrial network is interconnected and filamentous at G1/S but fragments during the S and G2/M phases, presumably to permit sorting to daughter cells. Pyruvate anaplerosis peaks at G1/S, consistent with generation of biomass for daughter cells, whereas mitochondrial Ca 2+ and respiration increase during S and G2/M, consistent with increased energy requirements for DNA and lipid synthesis. This synchronization approach may be of value to investigators performing live cell imaging of Ca 2+ or mitochondrial dynamics commonly undertaken in INS cell lines because without synchrony widely disparate data from cell to cell would be expected depending on position within cell cycle. Our findings also offer insight into why replicating beta-cells are relatively nonfunctional secreting insulin in response to glucose. They also provide guidance on metabolic requirements of beta-cells for the transition through the cell cycle that may complement the efforts currently restricted to manipulating cell cycle to drive beta-cells through cell cycle.